Epidemiology of Japanese encephalitis: past, present, and future prospects - Wang H; Liang G (Dove Medical Press, 2015)
Huanyu Wang,1,2 Guodong Liang1,21State Key Laboratory for Infectious Disease Prevention and Control (SKLID), Department of Viral Encephalitis, Institute for Viral Disease Control and Prevention, Chinese Center for Disease Control and Prevention, Beijing People’s Republic of China; 2Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, Hangzhou, People’s Republic of China Abstract: Japanese encephalitis (JE) is one of severe viral encephalitis that affects individuals in Asia, western Pacific countries, and northern Australia. Although 67,900 JE cases have been estimated among 24 JE epidemic countries annually, only 10,426 have been reported in 2011. With the establishment of JE surveillance and vaccine use in some countries, the JE incidence rate has decreased; however, serious outbreaks still occur. Understanding JE epidemics and identifying the circulating JE virus genotypes will improve JE prevention and control. This review summarizes the current epidemiology data in these countries. Keywords: Japanese encephalitis, Japanese encephalitis virus, acute encephalitis syndrome